Demonstration of seamless and wireless hand gesture control using leap motion thru an educational mobot soccer game - Abuan, Donabel D. (Animo Repository, 2023)
In recent years, the integration of advanced technologies in educational settings has revolutionized the learning experience. One such innovation is the utilization of gesture recognition systems to enhance interactivity and engagement. This study introduces a pioneering approach to leverage the Leap Motion device, a cutting-edge hand tracking technology, to facilitate seamless and wireless hand gesture control in the context of an educational mobot soccer game. From the leap motion device, the researcher collected information from dynamic hand gesture which includes coordinates, acceleration, and direction of fingers. In this research study covers the development process of hand gesture controlled-mobot including the integration of Leap Motion, Media Pipe Hands, and NodeMCU ESP8266. From the data collection process, it explains the static hand gestures (left index, right index, left nonindex, right nonindex), computing delta values (X and Z coordinates) based on detected pointing-up finger gestures and their role in controlling the mobot. Based from the performance average, from gesture to display output, the researcher analyze the impact of different delta values on the mobot’s speed and direction control, and compared the performance of Leap Motion and Media Pipe Hands for hand gesture recognition. Index Terms—Leap Motion, Media Pipe Hands, NodeMCU ESP8266).